[en] THE SOCIALS REPRESENTATIONS IN INTEGRAL HELP FAMILY PROGRAM: PAIF/ MIRACEMA - SAVIA DA SILVA OLIVEIRA (MAXWELL, 2004)
[pt] O presente estudo procura identificar as concepções de pobreza presentes na contemporaneidade bem como as representações sociais presentes nas relações vividas pelos diversos sujeitos. Para isso foram realizadas entrevistas junto aos profissionais que atuam no Programa de Atendimento Integral à Família, em Miracema. Nossas reflexões tiveram como base autores como Salama, Abranches, Rocha, Sen, Moscovici entre outros. Tendo por base às discussões contemporâneas do Estado brasileiro de amparo e assistência aos pobres o presente estudo buscou refletir acerca dessas noções de pobreza, identificando o quanto a abordagem conceitual pode influenciar as ações que pouco influenciam na vida dos sujeitos privados de uma plena participação na sociedade. === [en] The present study tries to identify the poverty conceptions presents in contemporary debate as well the socials representations presents in relationships lived by many subjects. For that center views were accomplished with professionals that work on Integral Help Family Program - Miracema. Our reflexions have for base in the author s vision as Salama, Abranches, Rocha, Sen, Moscovici an others. Having for base the contemporaries discussions in Brazilian state of help and assistance for the pours, the present study seek think about theses poverty conceptions, identifying how much theses conceptions have on influence in define actions that finished by a few influence in subjects lives that haven t on totally participation on society.